1998
DOI: 10.1084/jem.188.4.779
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection of Extrathymically Developed T Cells by Self-antigens

Abstract: Most T cells develop through the thymus, where they undergo positive and negative selection. Some peripheral T cells are known to develop in the absence of thymus, but there is insufficient information about their selection. To analyze the selection of extrathymically developed T cells, we reconstituted thymectomized male or female recipient mice with bone marrow cells of mice transgenic for male H-Y antigen–specific T cell receptor (TCR). It was revealed that the T cells bearing self-antigen–specific TCR were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…1 Fig. 1), neither of which developed in the absence of the thymus, as we have reported previously (7).…”
Section: All Of the Male Ag-specific T Cells In Male H-y Transgenic Msupporting
confidence: 63%
See 1 more Smart Citation
“…1 Fig. 1), neither of which developed in the absence of the thymus, as we have reported previously (7).…”
Section: All Of the Male Ag-specific T Cells In Male H-y Transgenic Msupporting
confidence: 63%
“…, and high levels of CD44 (CD44 high ) similar to the extrathymically developed T cells in normal mice (7). In this study, we first addressed whether all of the T3.70 ϩ CD8 ϩ cells in unmanipulated male H-Y transgenic mice have such phenotypes of surface molecule expression.…”
Section: All Of the Male Ag-specific T Cells In Male H-y Transgenic Mmentioning
confidence: 99%
“…␥␦ T cells and invariant NKT cells are also similar in their functions as innate lymphocytes that play a role in early protection against infection. Innate lymphocytes also include NK cells as well as memory phenotype CD8 T cells, which rapidly secrete IFN-␥ and a part of latter are suggested to be self-specific (45). NKT cells as well as IL-17-producing ␥␦ T cells express memory markers (43).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 von Boehmer et al 5 have shown that the development of CD8 lo cells is thymus dependent, since the cells are not found in male H-2 b H-Y nude mice. By contrast, Yamada et al 6 found that CD8 lo cells developed normally in thymectomized male but not female H-2 b mice. Another unusual feature of these CD8 lo T cells is that they proliferate in response to cytokines such as IL-2 and IL-15 in an antigen-independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The CD8 lo cells are selfreactive, as they expand after transfer into male but not female H-2 b nude mice. 5 These cells express high levels of CD44 5 and interleukin-2 receptor ␤ (IL-2R␤; CD122) 6 that are characteristic of memory T cells. However, they differ from conventional memory T cells in that they are more refractory to activation by antigen compared with naive T cells.…”
Section: Introductionmentioning
confidence: 99%